Integrierte, planare Leckwellenantennen für 3D-Millimeterwellen-Radarsysteme basierend auf dem holografischen Prinzip - Rusch, Christian (Karlsruher Forschungsberichte aus dem Institut für Hochfrequenztechnik und Elektronik, 2014)
In this thesis methods are presented to optimize the radiation characteristic of holographic antennas for the usage with frequency-modulated radar modules (FMCW principle). This combination allows the simultaneous measuring of distance and angular position to targets within a scenario, due to the frequency-scanning property of this antenna type. This work focuses on the design of the integrated, holographic antennas and their optimization in terms of important system parameters.